Evaluating farm-level livestock interventions in low-income countries: a scoping review of what works, how, and why - Lindahl, Johanna F.; Mutua, Florence K.; Grace, Delia (Cambridge University Press, 2020)
Livestock interventions can improve nutrition, health, and economic well-being of communities. The objectives of this review were to identify and characterize livestock interventions in developing countries and to assess their effectiveness in achieving development outcomes. A scoping review, guided by a search strategy, was conducted. Papers needed to be written in English, published in peer-reviewed journals, and describe interventions in animal health and production. Out of 2739 publications systematically screened at the title, abstract, and full publication levels, 70 met our inclusion criteria and were considered in the study. Eight relatively high-quality papers were identified and added, resulting in 78 reviewed publications. Only 15 studies used randomized controlled trial designs making it possible to confidently link interventions with the resulting outcomes. Eight studies had human nutrition or health as outcomes, 11 focused on disease control, and four were on livestock production. Eight interventions were considered successful, but only four were scalable. We found good evidence that livestock-transfer programs, leveraging livestock products for nutrition, and helping farmers manage priority diseases, can improve human well-being. Our report highlights challenges in garnering evidence for livestock interventions in developing countries and provides suggestions on how to improve the quantity and quality of future evaluations.